1980
DOI: 10.1111/1523-1747.ep12543557
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance or Hypersensitivity to 2,4-dinitro-1-fluorobenzene: The Role of Langerhans Cell Density within Epidermis

Abstract: Epidermal Langerhans cells have been implicated in the process by which animals skin painted with highly reactive haptens, such as DNFB, develop contact hypersensitivity. Compared to normal body wall skin, murine tail skin contains relatively few, unevenly distributed Langerhans cells; ultraviolet light exposure depletes the epidermis transiently of normal numbers of morphologically identifiable Langerhans cells. When mice are painted with DNFB on skin naturally or artificially depleted of Langerhans cells, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…These conclusions are supported by earlier observations, which have established the presence of two different DC compartments in the skin: LC restricted to the epidermis (27) and dermal DC localized in the perivascular area of the dermis (28,29). The observation that LCs are able (30), but not essential, to induce contact hypersensitivity suggested also the participation of dermal DCs in the regulation of skin immune reactions (31). Unfortunately, the phenotypic characterization of mouse dermal DCs has been hampered to date by the lack of unique serological markers, unlike in human system, in which CD36 can be used as a typical marker for these cells (29).…”
Section: Discussionsupporting
confidence: 86%
“…These conclusions are supported by earlier observations, which have established the presence of two different DC compartments in the skin: LC restricted to the epidermis (27) and dermal DC localized in the perivascular area of the dermis (28,29). The observation that LCs are able (30), but not essential, to induce contact hypersensitivity suggested also the participation of dermal DCs in the regulation of skin immune reactions (31). Unfortunately, the phenotypic characterization of mouse dermal DCs has been hampered to date by the lack of unique serological markers, unlike in human system, in which CD36 can be used as a typical marker for these cells (29).…”
Section: Discussionsupporting
confidence: 86%
“…Although, several studies have described LCs as potent APCs (51)(52)(53)(54)(55)(56), recent observations propose a rather tolerogenic role for LCs. Using pathogenic infections or LC-depleted tg mice, recent studies implicate LCs as having an immune suppressive role, and they point toward DDCs and CD8␣␣ ϩ blood-derived DCs as the main inducers of efficient antiviral, allogeneic, and hypersensitivity immune responses (32,36,37,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, decreased skin reactivity to various antigens such as dinitroclorobenzene and tuberculin [known to induce a delayed type of hyper sensitivity (DTH) reaction] can be demonstrated in HD and CAPD patients [22], Interestingly, a diminished reaction to intradermally applied antigens, such as dinitrofluorobenzene, has been associated with a decreased epidermal LC density [23]. It has been shown that LC-depleted skin of mice is unresponsive to chemical contact sensitizers as dinitrofiuorobenzene [24],…”
Section: Discussionmentioning
confidence: 99%